A dynamic relationship between mucosal T helper type 17 and regulatory T-cell populations in nasopharynx evolves with age and associates with the clearance of pneumococcal carriage in humans. (August 2016) - Mubarak, A.; Ahmed, M.S.; Upile, N.; Vaughan, C.; Xie, C.; Sharma, R.; Acar, P.; McCormick, M.S.; Paton, J.C.; Mitchell, T.; Cunliffe, N.; Zhang, Q.
Abstract: Pneumococcal carriage is common in young children, which may account for the high incidence of disease in this age group. Host factors determining the clearance of carriage in humans remain unclear. We aimed to study the relationships between T helper type 17 (Th17) and Foxp3 + regulatory T (Treg) cells in nasopharynx-associated lymphoid tissue (NALT) and carriage in children and adults. Frequencies of Th17 and Treg cells in NALT were analysed by flow cytometry in association with age and pneumococcal carriage status. Cytokine responses following pneumococcal stimulation were analysed by cytometric beads array. The frequencies of Th17 and Treg cells in NALT were inversely correlated ( R –0.60). Whereas Treg cell frequency decreased with age ( R –0.63), both Th17 and the Th17: Treg ratio increased with age ( R 0.62 and R 0.64, respectively). Also, the Th17: Treg ratio was higher in carriage-negative than in carriage-positive children (p <0.01). Pneumococcal stimulation of tonsillar cells increased both Th17 and Treg cell numbers, but the Th17: Treg ratio and pattern of cytokine responses differed between carriage-negative and carriage-positive children. The former showed markedly higher Th17: Treg and interleukin-17A: interleukin-10 ratios than in the latter (p <0.01). Pneumococcal stimulation also induces Th17, although the capacity of this Th17 differentiation from naive T cells of young children was low, but increased with age. We demonstrated a dynamic relationship between Th17 and Treg cells in human nasopharynx that evolves with age. The balance between Th17 and Treg cells in NALT appears to be a major host factor closely associated with the clearance of Streptococcus pneumoniae from the nasopharynx.